STUDY OF THE ANESTHETIC SOLUTIONS` EFFECT ON THE ULTRASTRUCTURE OF THE MUCOUS MEMBRANE OF THE GUMS AND MUSCLES OF RATS - Anisimov, M.V.; Shnaider, S.A.; Anisimova, L.V.; Reyzvikh, O.E.; Molchanyuk, N.I. (World of Medicine and Biology, 2021)
Improving the safety and efficiency of anesthesia in the treatment of oral diseases is one of the pressing problems of modern dentistry, where the choice of anesthetic solution is important, taking into account its physicochemical properties. The presence of vasoconstrictors in the local anesthetic solution improves the quality of anesthesia, but at the same time creates a number of relative and absolute contraindications for the use of such drugs. A reliable resolution to this problem can be the development of a new composition of anesthetic solution based on sodium hyaluronate and without the use of vasoconstrictors. To study the direct effect of the proposed solution on soft tissues in the area of its administration, their ultrastructure was researched. Analysis of the results of the study showed that changes in the ultrastructure of tissues in the area of administration of solutions occurred in all experimental groups of animals in comparison with the intact group and had both common features and certain differences. Ultrastructural changes in the mucous membrane and muscles in animals after the introduction of a new composition of the anesthetic were characterized by the presence of mitochondrial and ribosomal reactions, which may be due to the activation of hyaluronidase and protein synthesis processes. 7 days after administration of the solutions, normalization of the ultrastructure of the mucous and masticatory muscles was observed in all experimental animals, which indicates their reverse and functional nature.
Keywords: sodium hyaluronate; electron microscopy; tissue ultrastructure; dental anesthetic; experimental animals